Comparison of somatotype profiles and dietary intake of football athletes in different playing levels in Indonesia - Mirza Hapsari Sakti Titis Penggalih; Kurnia Maratus Solichah; Mustika Cahya Nirmala Dewinta; Ibtidau Niamilah; Almira Nadia; Diana Pratiwi; Dessy Hosianna; Arum Darmastuti; Annisa Prihastin; Naila Syarifah; Ratna Kusuma Ningrum; Vigur Dinda Yulia Reswati; Nia Bactiar (Jurnal Gizi Klinik Indonesia, 2021)
Background: Anthropometry characteristic was significantly correlated with nutrition status, and both factors significantly contributed to athletes' sports performance. Somatotype as one of the anthropometric values can be used as screening or “diagnosis” in selecting new talents. The changes in athletes’ body composition by inadequate dietary intake and over-consumption relate to the performance quality of athletes. Objective: The study aimed to compare football athletes' somatotype profiles and dietary intake in different playing levels in Indonesia. Methods: A total of 112 adolescent football athletes in 4 playing levels; elite national team (ENT), advanced senior team (AST), advanced junior team (AJT), and amateur college athletes (ACT), performed somatotype measurement and dietary intake assessments using 3x24-h food recall. One-way analysis of variance (ANOVA) was conducted to illustrate the difference among ENT, AST, AJT, and ACT groups, while a post-hoc test was used to verify pairwise comparison. Results: All groups showed a significant difference in somatotype profiles and dietary intake. The somatotype profile of ENT group, categorized as balanced mesomorph (2.5-5.2-2.2), was the closest to the ideal profile of elite football athletes and was the most mesomorph among other groups. The somatotype of the AST group was the least mesomorph (1.5-3.2-3.0). Adequate energy intake was found only in the ENT group, whereas inadequate (<80%) in other groups. None of the groups consume an adequate amount of carbohydrates. The lowest dietary intake was found in the lowest playing level group, ACT. The somatotype profile and dietary intake of the ENT group were the most optimum compared to other groups, although the excess intake of fat should be noticed. Conclusions: The somatotype profile of elite athletes in the ENT group was the closest to the ideal somatotype of elite football athletes in high-level competition. Dietary intake in the ENT group was also the most adequate, although the excess fat intake should be noticed.